Effects of Microplastics and Nanoplastics in Agro-ecosystems and Human Health: A review - Rathiverni, R.; Jayawardana, N.U. (University of Jaffna, 2023)
Life on land and ocean is being threatened by microplastics (MPs) and nanoplastics (NPs). Despite, the fate and effects of MPs and NPs in agro-ecosystems have not been clearly understood. However, recent studies showed that these polymers can be transported and accumulated in food crops, humans, and other organisms. The introduction of plastics into terrestrial land has led to the accumulation of MPs and NPs in food crops. The bioaccumulation has been found in stems, leaves, flowers, and fruits. Thus, causes a change in physicochemical activities in plants that leads to a decline in crop production. Further, MPs accumulation in human placenta and breast milk have been evidently proven in recent studies. MPs themselves are being potential vectors of pollutants, including anti-resistance genes, harmful microbes, heavy metals, and carcinogenic compounds. Alarmingly, these pollutants can be horizontally transferred to organisms along with the MPs and remain intact throughout the food chain. Poor solid waste management, inadequacy in plastic recycling, and application of MPs contaminated compost in agricultural practices are the major entry points of MPs into the agro-ecosystem. The collection of these results in this study will help both ongoing and upcoming investigations on bioaccumulation of MPs and NPs in crops and their movement through the food chain.
Keywords: Microplastics; Crop production; Bioaccumulation; Human health; White pollution